Labor market transitions in Peru - Javier Herrera; Gerardo David Rosas Shady (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2003)
Traditional labor market analysis based solely on the net unemployment rate fails to explain the apparent paradox between a relatively moderate unemployment rate in Peru (around 10%, with a weak sensibility to wide macroeconomic fluctuations), and the fact that unemployment is one of the major issues in Peru. One possible explanation is that this static indicator of cross section net unemployment balance is compatible with high flows in and out of employment states. To address these issues we needed to conduct a dynamic analysis using panel data. Using the Peruvian national household survey (ENAHO), we constructed a panel of working age individuals at the national level for the period 1997-1999. Like previous work in developing countries, we found that there is an important degree of job mobility in Peru. We also found that most of the transitions occur between employment and inactivity instead of between employment and unemployment. We also showed that the rate of permanent unemployment is very low so that unemployment would be essentially a frictional phenomenon. Further, considering the different transition states, we elaborated an unconditional transition profile, including individual and household characteristics, like gender, age and education levels for example, associated with each transition status. Finally, after examining these labor market transitions and the possible sample selection bias, we estimated a multinomial logit model. This model allowed us to appreciate the (conditional) incidence of individual and household characteristics as well as the effects of different shocks on the labor transition states.
Keywords: 330